Alliance for progress in colombia (2010)
The present article analyzes the way in which the program Alliance For Progress was implemented and executed in Colombia, with the aim of establishing to what extent and how this kind of external intervention by The United States had or not an effect on the process of construction and transformation of the country's institutional architecture during the sixties.To such aim, the basis of Alliance For Progress, starting from the analysis of the U.S. foreign policy toward Latin America in the early years of the Cold War, is presented. Then, the implementation of Alliance For Progress in Colombia through the 60s is examined. Finally, a turn is made, from the results of the program and its implications to the understanding of international intervention within the process of state construction in Colombia.